Post-fledging habitat selection of a Purple Heron Ardea purpurea revealed by GPS/GSM telemetry (Avocetta, 2021)
The Purple Heron is a species of conservation concern in Europe, mainly threatened by the progressive degradation and reduction of wetlands. For future conservation practices, it is of pivotal importance to gather detailed knowledge of its habitat preferences. In June 2018, a nestling of Purple Heron from a sub-Alpine Lake in Northern Italy was equipped with a GPS/GSM device. Habitat selection during the post-fledging period (mid-July to mid-October) was analysed by superimposing the GPS locations to a fine-grained field-based map,discerning 14 habitat classes as well as narrow (
Keywords: Typha sp.; Phragmites australis; waterbirds; movement ecology; inland wetlands; ditches; Ardea purpurea